2016
DOI: 10.5812/hepatmon.44564
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of 12 Weeks of Sofosbuvir, Daclatasvir, and Ribavirin in Treating Hepatitis C Patients with Cirrhosis, Genotypes 1 and 3

Abstract: Background: The combination of sofosbuvir and daclatasvir can be used to treat all genotypes of hepatitis C. Current guidelines for treating hepatitis C cirrhosis do not clarify weather 12 weeks or 24 weeks of treatment is appropriate. Objectives: In the present study, we aimed at evaluating the efficacy of sofosbuvir, daclatasvir, and ribavirin given for 12 weeks in treating cirrhotic patients with hepatitis C genotypes 1 and 3 infections. Methods: One hundred patients with hepatitis C and cirrhosis infected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 20 publications
3
25
1
Order By: Relevance
“…Of the 8262 citations and 23 additional manually searched articles evaluated, we included 41 studies published in full articles (Figure ) . Of those, four studies were used only to extract data for subgroup analysis because the overall SVR data were already reported and extracted for overlapping populations in other four included studies .…”
Section: Resultsmentioning
confidence: 99%
“…Of the 8262 citations and 23 additional manually searched articles evaluated, we included 41 studies published in full articles (Figure ) . Of those, four studies were used only to extract data for subgroup analysis because the overall SVR data were already reported and extracted for overlapping populations in other four included studies .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Merat et al reported an increase in HCV seroprevalence in the country (19). All Iranian HCV patients were treated using SOVODAK -a single pill containing Sofosbuvir and Daclatasvirwhich has been shown to provide a 98% sustained virologic response (SVR) in HCV patients (20). Therefore, it is expected in this case that the WHO target for 2020 will be reached.…”
Section: Discussionmentioning
confidence: 99%
“…In HCV-1 infected patients with a previous history of PegIFN + RBV therapy and/or cirrhosis (child A), intensification of 12 weeks of SOF/LDV or SOF + DCV with adding RBV is recommended, however, the latter groups can be treated with 12 weeks of SOF/VEL without addition of RBV (2,11,12). Moreover, decompensated cirrhosis (child B and C) patients with HCV-1 infection can be treated for 24 weeks of SOF/LDV, SOF + DCV or SOF/VEL with addition of RBV (4,6,11,13). However, in RBV-intolerant cases, treatment can be extended to 24 weeks of SOF/LDV, SOF + DCV, or SOF/VEL without RBV.…”
Section: Update On Treatment Of Hcv Genotype 1 and 4 Infectionsmentioning
confidence: 99%
“…Since 2015, various all-oral regimens approved for treatment of HCV with introduction of new treatment regimens in 2017 including sofosbuvir/velpatasvir/voxilaprevir (SOF/VEL/VOX) and glecaprevir/pibrentasvir (GLE/PIB). Hopefully, the generic DAAs including SOF, sofosbuvir/ledipasvir fixed dose combination (SOF/LDV), daclatasvir (DCV) and sofosbuvir/daclatasvir fixed dose combination (SOF/DCV) are available in Iran since 2016 (5,6). With availability of these generic DAAs, Iranian healthcare system decided to eliminate hepatitis C in the country with an estimation of 186000 infected patients (7,8).…”
Section: Introductionmentioning
confidence: 99%